ANALISIS MAKNA TARI MOGAELE DI DESA ORAHILI FAU KECAMATAN FANAYAMA - Merdian Telaumbanua (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2025)
This research is motivated by the meanings of the Mogaele dance found in Orahili Fau village, Fanayama district. This research aims to describe the meaning of the Mogaele dance in Orahili Fau village, Fanayama District in semiotic studies. This type of research is descriptive qualitative research. The subject of this research is the meaning of the Mogaele dance. The results of the research can show that in Orahili village there is a hidden meaning to the Mogaele dance movements, consisting of: Slow walking foot movements, arm swinging movements, tiptoe movements, straight sideways movements, and afo/betel giving movements. The suggestions put forward in this research are 1) It is recommended that students carry out further research, both in the field that has been studied and in other fields, to develop knowledge about the meaning of Mogaele dance. 2) There is attention to preserving the meaning of Mogaele dance, so that Mogaele dance remains preserved.